Ceramides bind VDAC2 to trigger mitochondrial apoptosis - Shashank Dadsena (Nature Portfolio, 2019)
Ceramides are lipids that act directly on mitochondria to trigger apoptosis, but the underlying mechanism remains largely unclear. Here authors use a photoactivatable ceramide probe combined with a computation approach and functional studies to identify the voltage-dependent anion channel VDAC2 as a direct effector of ceramide-mediated cell death.